Mind over matter : - Baker, Ronald J. (John Wiley & Sons Inc, 2008)
Praise for Mind Over Matter Why Intellectual capital is tHe Chief Source of Wealth "Ron Baker has written another great book on the thoughts and theories on intellectual capital.As usual, he has an awesome depth of content, knowledge, and thought. A great read." -Reed Holden, founder, Holden Advisors Corp., www.holdenadvisors.com, and coauthor, The Strategy and Tactics of Pricing and Pricing with Confidence: 10 Ways to Stop Leaving Money on the Table "At a time when the virtues that made America great--individualism, hard work, and free trade--are openly debated by well-meaning politicians, Ron Baker gives us Mind Over Matter. It is a story detailing the triumph of human spirit, imagination, and creativity. Ron tells us what the 'knowledge economy' really means. He gives a prescription for transforming human and intellectual capital into the foundation for sustainable prosperity. Mind Over Matter is a provocative book deserving of a thoughtful read. It is a timeless message to be treasured for generations." -Robert G. Cross, Chairman and CEO, Revenue Analytics, Inc., www.revenueanalytics.com "Ron Baker is an absolute master at challenging the 'physical fallacy,' e.g., the basis on which we assign value to businesses by focusing on tangible rather than intangible assets. This book builds on his previous books and helps the reader understand how critical intellectual capital is to the key to success in the twenty-first century. Ron pulls from the greatest business thinkers and economists,?from Drucker to Karl Sveiby as well as current company success stories to fund his rich gold mine of proof. The biggest benefit of the book is to change the paradigm of those who are the passive keepers of the 'books.' This is a must-read for anybody who wants to flourish in the age of intellectual capital." -Sheila Kessler, PhD, President, Competitive Edge, www.CompetitiveEdge.com "This book helps us understand some of the origins and sources that have led Ron Baker to the many contributions he has made to our understanding of good practice in running professional businesses." -David Maister, author and leading consultant to professional firms www.davidmaister.com "Reading Ron Baker's book was the only delightful incident that robbed my sleep on the flight to Frankfurt today. It was sheer pleasure-I must have entertained or annoyed fellow passengers with repeated nodding and several exclamations. Baker has a terrific style that captures my mind while he entertains and educates by showing lines of connection between authors, incidents, and theories that I have never seen before. He hardly uses the 'You have to do this and that' approach, which I despise in most business books. I sum it up in two words: outstanding stuff!" -Friedrich Blase, Kerma Partners, www.kermapartners.com "This is a wonderful read for anyone who wants to explore the power of constructive thinki